Qualitative research from start to finish - Yin, Robert K. (New York : The Guilford Press, 2011)
"I know of no other book that so clearly, logically, and thoroughly walks the reader through every step of the qualitative research process. The book is state of the art in terms of current trends, in qualitative research, and its review of novel and classic qualitative studies is second to none. Despite his stature as a world-renowned qualitative researcher, Yin's approach and writing style are so accessible that readers will feel like he is speaking directly to them in a small seminar. Very helpful features include preview questions, vignettes, chapter summaries of key concepts learned, and practical exercises"--
"This book makes qualitative methods accessible to a broad audience. It includes practical advice and connects new researchers with well-chosen examples from a diverse array of rigorous qualitative studies. The discussion of the analysis process is a major strength"--
"The pedagogical features are good and follow a learn-by-doing model; the helpful vignettes bring in real-world examples. Students who are new to the methods will be inspired by reading about studies on topics they are interested in or have experienced themselves"--
This lively, practical text presents a fresh and comprehensive approach to doing qualitative research. The book offers a unique balance of theory and clear-cut choices for customizing every phase of a qualitative study. A scholarly mix of classic and contemporary studies from multiple disciplines provides compelling, field-based examples of the full range of qualitative approaches. Readers learn about adaptive ways of designing studies, collecting data, analyzing data, and reporting findings. Key aspects of the researcher's craft are addressed, such as fieldwork options, the five phases of data analysis (with and without using computer-based software), and how to incorporate the researcher's "declarative" and "reflective" selves into a final report"--
What is qualitative research--and why might you consider doing such research? -- Equipping yourself to do qualitative research -- How to start a research study -- Choices in designing qualitative research studies -- Doing fieldwork -- Data collection methods -- Recording data -- Analyzing quantitative data, I: compiling, disassembling, and reassembling -- Analyzing qualitative data, II: interpreting and concluding -- Displaying qualitative data -- Composing research, to share it with others -- Broadening the challenge of doing qualitative research.
ODL_2016/2017.
Includes bibliographical references and indexes.
Keywords: Qualitative research; Research -- Methodology; Social sciences -- Research; Qualitative Research; Recherche qualitative; Sciences sociales -- Recherche; Qualitative research; Research -- Methodology; Social sciences -- Research